2017
DOI: 10.1039/c7ra05693a
|View full text |Cite
|
Sign up to set email alerts
|

A sub-acute oral toxicity analysis and comparative in vivo anti-diabetic activity of zinc oxide, cerium oxide, silver nanoparticles, and Momordica charantia in streptozotocin-induced diabetic Wistar rats

Abstract: Type 2 diabetes mellitus (T2DM) is one of the most threatening, non-communicable ailments worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 23 publications
1
24
0
2
Order By: Relevance
“…The efficacy of ZnO QDs in attenuating pancreatic damage in a rat model of treptozotocin-induced diabetes was also settled one year later by Kandeel et al [ 113 ]. Other comparative studies including ZnO QDs for antidiabetic studies have been performed [ 114 ]. In 2016, Abu-Risha et al went a step further and studied the antidiabetic effect of a co-administered treatment based on ZnO QDs and Vildagliptin, a standard antidiabetic drug.…”
Section: Zno Nanoplatforms For Diabetes Treatmentmentioning
confidence: 99%
“…The efficacy of ZnO QDs in attenuating pancreatic damage in a rat model of treptozotocin-induced diabetes was also settled one year later by Kandeel et al [ 113 ]. Other comparative studies including ZnO QDs for antidiabetic studies have been performed [ 114 ]. In 2016, Abu-Risha et al went a step further and studied the antidiabetic effect of a co-administered treatment based on ZnO QDs and Vildagliptin, a standard antidiabetic drug.…”
Section: Zno Nanoplatforms For Diabetes Treatmentmentioning
confidence: 99%
“…The FE-SEM pictures show the uniform distribution of ZnO NPs and their partially spherical and cubic shape. The bio-synthesized NPs were shown to have a smooth surface due to the presence of the biological compounds (18)(19)(20).…”
Section: Fig 1 Xrd Spectrum Of Synthesized (A) Ag and (B) Znomentioning
confidence: 99%
“…The study of the effect of drug toxicity and its side effects are other important topics addressed in our research. In that connection, a sub-acute oral toxicity analysis by zinc oxide NPs antidiabetic activity in vivo carried out by Shanker et al is noteworthy [23]. Furthermore, a study by Jacobsen et al showed that the toxicity of zinc oxide NPs appeared to be dose dependent [24].…”
Section: Introductionmentioning
confidence: 99%